Concept, Implementation, and Development of Productive Zakat Management for Social, Educational, and Humanitarian - Muhammad Iqbal; Kaleem Chaghtai; Aisyah Abdul Jabbar; Meguellati Achour; M Muthoifin; Edwards Geraldine (Demak Universal Journal of Islam and Sharia, 2024)
The management of zakat funds for education can be realized in the form of an education care program by providing education costs to students who come from poor families. However, zakat institutions that distribute aid for education are still widely used by the community for their own operational needs. Research was conducted to gain an understanding of the management of zakat funds in education at the Yatim Mandiri zakat institution, as well as the perspective of Sharia economic law in managing zakat at this institution. The research method used is qualitative with a descriptive approach through interviews and observation.  The research results show that there are five fund management procedures implemented by schools, as determined by the Yatim Mandiri Foundation, namely: financial planning, receiving funds, disbursing funds, accountability for funds, and financial control. The distribution of zakat funds for education by Yatim Mandiri is included in the productive zakat given directly by mustahik, namely schools, as a real investment which is considered to be on target.